Comprehensive assessment of pain characteristics, quality of life, and pain management in cancer patients: a multi-center cross-sectional study - Shrestha, Sunil; Sapkota, Simit; Teoh, Siew Li; Kc, Bhuvan; Paudyal, Vibhu; Lee, Shaun Wen Huey; Gan, Siew Hua (Quality of Life Research, 2024)
Abstract Introduction Pain is the most common complaint among cancer patients, significantly impairing their health-related quality of life (HRQOL). There is limited evidence on the characteristics of pain among cancer patients in Nepal with low-resource settings. Objectives The primary objective of this study was to evaluate the clinical characteristics of pain, factors influencing pain intensity, and the association of pain severity with quality of life (QoL) among cancer patients. Secondary objectives included investigating perceived barriers to pain management and medication adherence among these patients. Methods This multi-center, cross-sectional study enrolled adult patients (over 18 years old) with reported cancer diagnoses experiencing pain. Socio-demographic characteristics (e.g., age, gender, educational status), clinical characteristics (e.g. cancer diagnosis, staging), and pain characteristics (e.g., duration, type, location, medicines used for pain management, etc.) were recorded. Outcomes were assessed using the Numeric rating scale (NRS), Pain management Index, European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire, Barriers Questionnaire II, Medication Adherence Rating Scale, and Hospital Anxiety and Depression Scale. Results Four hundred and eight patients participated in the study. The mean ± SD age was 54.87 ± 15.65, with 226 patients (55.4%) being female. The most common cancer diagnoses were cervical (17.6%), lung (11.8%), and colon/rectum (12.0%) cancers. The most common pain locations were the head and neck (27.0%); a majority (55.6%) reported pain duration of more than 3 months. Nociceptive pain was reported by 42.4% of patients; the mean ± SD of NRS was 4.31 ± 2.69, with 32.4% of patients experiencing moderate pain. Patients with mixed pain type (B = 1.458, p < 0.001) or pain in multiple sites (B = 1.175, p < 0.001), lower Karnofsky Performance Status (KPS) (B = -1.308, p < 0.001), and specific cancer diagnoses such as prostate (B = -2.045, p = 0.002), pancreatic (B = 1.852, p = 0.004), oesophageal (B = 1.674, p = 0.012), and ovarian cancer (B = 1.967, p = 0.047), experienced varying degrees of increased NRS score. The combined chemotherapy and radiotherapy treatment modality was associated with a lower NRS score (B = -0.583, p = 0.017). A significant inverse relationship was observed between pain severity and global health status/QoL (B = -37.36, p < 0.001. Key barriers to pain management included moderate perceptions of physiological effects, communication issues between doctors and patients, and concerns about the harmful effects of pain medicine. The prevalence of non-adherence to pain medications was 13.97%. Conclusion In conclusion, this study highlights the multi-faceted nature of pain management and QoL for cancer patients in Nepal with low-resource settings. These findings underscore the multifactorial nature of pain perception in cancer patients, with mixed pain types, pain in multiple sites, lower KPS, and specific cancer diagnoses, all contributing significantly to pain severity. Additionally, pain severity was associated with declining QoL. These findings contribute valuable insights into the complex aspects of cancer pain and its broader implications for the well-being of patients, offering a foundation for targeted interventions and improved pain management strategies in the context of cancer care in low-resource settings.